Landscape attributes effects on Ateles fusciceps presence patterns in northwestern Ecuador - Medrano-Vizcaíno, Pablo (2018)
In this work, I investigate the effect of some landscape variables (rivers, agricultural lands, anthropic areas and native forest) on the presence patterns of spider monkey, Ateles fusciceps, in the northwestern Ecuador. Geographical records collected in field and others from previous studies were used to conduct this study. Effects of proximity of each variable to presence of A. fusciceps were assessed with Student T tests. The best model and the most important variables were identified using logistic regressions and the Akaike Information Criterion (AIC). The results showed that agricultural lands and anthropic zones were from the primate presence points, suggesting a negative effect on A. fusciceps. I also found that A. fusciceps prefers sites near rivers, this observation has not been reported in previous studies. Two important models were found to predict the presence of A. fusciceps, the first one was composed by three variables: native forest, rivers and anthropic areas (AICw= 0.48) and the second model was composed by the four variables: native forest, rivers, anthropic areas and agricultural lands (AICw= 0.34). The results of this work will contribute a basis for future studies aimed on A. fusciceps conservation.